2014
DOI: 10.1109/tnano.2013.2292610
|View full text |Cite
|
Sign up to set email alerts
|

Video-Rate Lissajous-Scan Atomic Force Microscopy

Abstract: Abstract-Raster scanning is common in atomic force microscopy (AFM). The nonsmooth raster waveform contains highfrequency content that can excite mechanical resonances of an AFM nanopositioner during a fast scan, causing severe distortions in the resulting image. The mainstream approach to avoid scan-induced vibrations in video-rate AFM is to employ a highbandwidth nanopositioner with the first lateral resonance frequency above 20 kHz. In this paper, video-rate scanning on a nanopositioner with 11.3-kHz resona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 44 publications
0
34
0
Order By: Relevance
“…However, the implementation of the Lissajous scanning method allows the scan speed to be increased significantly further above this value. 25,27 The Lissajous pattern is obtained in this case by driving the orthogonal axes of the nanopositioner with sinusoidal signals of different frequencies ( f x and f y ) and identical phase shifts (0 • ). In (2), the actuation signals V x and V y are presented for the X and Y axes, respectively.…”
Section: Lissajous Scan Principle and Open-loop Trackingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the implementation of the Lissajous scanning method allows the scan speed to be increased significantly further above this value. 25,27 The Lissajous pattern is obtained in this case by driving the orthogonal axes of the nanopositioner with sinusoidal signals of different frequencies ( f x and f y ) and identical phase shifts (0 • ). In (2), the actuation signals V x and V y are presented for the X and Y axes, respectively.…”
Section: Lissajous Scan Principle and Open-loop Trackingmentioning
confidence: 99%
“…However, there has been recent interest in the use of non-raster scan methods for AFM, which include the implementation of spiral, cycloid, and Lissajous scanning methods. [25][26][27][28][29] The Lissajous pattern is constructed through the use of two pure tone sinusoidal signals with slightly differing frequencies or phases as the reference signal for each axis. It has been shown that this scan method provides a number of distinct advantages compared with raster scanning including significantly increased scanning speeds, improved image quality, and a simpler control implementation.…”
Section: Introductionmentioning
confidence: 99%
“…To simplify the representation, define to be an unknown time-varying function of the system states, so that Eq. (9) can be simplified as: (10) Note that is a positive diagonal matrix since the piezoelectric coefficients and equivalent mass of the piezoelectric scanner are all positive values. Substituting Eq.…”
Section: B Problem Formulationmentioning
confidence: 99%
“…Therefore, selecting an appropriate scanning trajectory without inducing mechanical vibration is essential to achieving reasonable scanning speeds without sacrificing image quality. Several smooth scanning trajectories have been proposed to improve the scanning speeds in AFMs without any hardware modification, including spiral scanning [7] as well as sinusoidal [8], cycloid-like [9], and Lissajous scan paths [10]. In this research, in order to increase the scan rate of AFM, we design an internal model principle (IMP) advanced controller based on the dynamic characteristics of Lissajous trajectory to realize a fast AFM image scanning by reducing the mechanical vibration of the xy-piezoelectric canner.…”
Section: Introductionmentioning
confidence: 99%
“…The primary advantages of raster scanning are the constant velocity and simple image reconstruction which is due to regularly sampled data appearing on a square grid. Similarly, the application of Lissajous scanning pattern in SPM can be found in [24][25][26]. Sinusoidal raster scanning involves driving the x-axis (fast axis) with a sinusoidal trajectory while shifting the sample in steps or continuously in the y-axis (slow axis) [14][15][16].…”
Section: Introductionmentioning
confidence: 99%